KAJIAN MUZARA'AH DAN MUSAQAH (HUKUM BAGI HASIL PERTANIAN DALAM ISLAM) THE MUZARA'AH DAN MUSAQAH STUDY (Agricultural Production Sharing Law In Islam) - Shania Verra Nita (Qawanin: Jurnal of Economic Syaria Law, 2020)
Tujuan dari penelitian ini untuk menganalisis kesesuaian sistem kerjasama bagi hasil dalam pertanian petani muslim menurut Islam atau fiqh muamalah. Kajian ini berisi tentang faktor-faktor yang melatarbelakangi kerjasama penggarapan lahan, pendapatan pemilik lahan dengan petani penggarap, serta kesesuaian hukum muzara'ah dan musaqah dalam kajian hukum Islam. Dari hasil penelitian ini ditemukan bahwa faktor yang melatarbelakangi adanya kerjasama dan tolong menolong antara kedua belah pihak yang berakad. Perbedaan antara kerjasama bentuk muzaraâ€™ah dan musaqah terletak pada pertanggungjawaban biaya selama penggarapan apakah ditanggung oleh pemilik lahan atau petani penggarap, jangka waktu penggarapan lahan serta porsi bagi hasil. Hasil penelitian ini menunjukkan adanya kesesuaian sistem atau cara kerjasama bagi hasil pertanian ini dengan aturan fiqih Islam, karena syarat-syarat yang berlaku telah terpenuhi dalam hukum syarâ€™i. Kegiatan bagi hasil ini mengandung prinsip bahwa ada unsur kerelaan antara kedua belah pihak, saling menguntungkan, serta kegiatan yang sesuai dengan kandungan Al-Qurâ€™an dan Hadits dalam bermuamalah. This study aims to identify and explain the suitability of the production-sharing cooperation system in Muslim farmer agriculture that has been carried out for generations by means of agricultural production sharing in Islam or fiqh muamalah and to determine the factors behind the cooperation in cultivating land, to find out the difference between its contribution to increasing the income of landowners and tenant farmers, as well as the legal bases of muzara'ah and musaqah in the study of Islamic law. From the results of this study it was found that the factors behind the cooperation in cultivating land in the form of muzara'ah and musaqah were the economic value of the land and the help between the land owner and the tenants. The difference between cooperation in the form of muzara'ah and musaqah lies in terms of accountability for costs during cultivation, whether it is borne by the land owner / cultivator, the time of cultivating the land and the percentage of the harvest. The results of this study indicate the compatibility of the system or way of cooperation for agricultural produce with the principles of Islamic muamalah fiqh, because it has met the applicable requirements in syar'i law and contains the principle that there is an element of willingness and mutual benefit, and habits ('urf) which is not against the law in the Koran and Hadith, and also does not contain madharat.